The antipsychotic-like effects of positive allosteric modulators of metabotropic glutamate mGlu(4) receptors in rodents - Sławińska, Anna (Blackwell Publishing Ltd, 2013)
BACKGROUND AND PURPOSE: Because agonists at metabotropic glutamate receptors exert beneficial effects in schizophrenia, we have assessed the actions of Lu AF21934 and Lu AF32615, two chemically distinct, selective and brain-penetrant positive allosteric modulators (PAMs) of the mGlu(4) receptor, in several tests reflecting positive, negative and cognitive symptoms of schizophrenia in rodents. EXPERIMENTAL APPROACH: Hyperactivity induced by MK-801 or amphetamine and head twitches induced by 2,5-dimethoxy-4-iodoamphetamine (DOI) in mice were used as models for positive symptoms. Disruption of social interaction and spatial delayed alternation tests induced by MK-801 in rats were used as models for negative and cognitive symptoms of schizophrenia, respectively. KEY RESULTS: Lu AF21934 (0.1–5 mg·kg(−1)) and Lu AF32615 (2–10 mg·kg(−1)) dose-dependently inhibited hyperactivity induced by MK-801 or amphetamine. They also antagonized head twitches and increased frequency of spontaneous excitatory postsynaptic currents (EPSCs) in brain slices, induced by DOI. In mice lacking the mGlu(4) receptor (mGlu(4)(−/−)) mice, Lu AF21934 did not antagonize DOI-induced head twitches. MK-801-induced disruption in the social interaction test was decreased by Lu AF21934 at 0.5 mg·kg(−1) and by Lu AF32615 at 10 mg·kg(−1). In the delayed spatial alternation test, Lu AF21934 was active at 1 and 2 mg·kg(−1), while Lu AF32615 was active at 10 mg·kg(−1). CONCLUSIONS AND IMPLICATIONS: We propose that activation by PAMs of the mGlu(4) receptor is a promising approach to the discovery of novel antipsychotic drugs.